Contamination Level Analysis of the Klinajau River in Dun Village, Muara Ancalong District, East Kutai Regency, East Kalimantan Province. - Shalehudin Denny Maruf Denny; Wardatul Hidayah; Daru Kelvin Argya Pradana; Diepa Febriana Wulandari (Politeknik Pertanian Negeri Samarinda, 2025)
Water is the most fundamental necessity for humans and other living beings. The growing population increases the demand for water resources. Rivers are one of the primary sources of water to fulfill human needs. Currently, the main issue is that surface water is often polluted, reducing its quality. The Klinjau River, located in Muara Dun Village, plays a vital role, particularly in supporting the quality of life for various community activities. This study aims to analyze the water quality Index and contamination level in Klinjau River at Muara Dun Village. The analysis results of the Klinjau River water show average pH values for the upstream, midstream, and downstream points as 7.183, 7.475, and 7.459, respectively. The average TDS levels at the upstream, midstream, and downstream points are 5.11, 5.03, and 5.30 mg/l, respectively. The average DO levels in the river are 51.96, 50.95, and 47 mg/l, respectively. Based on these findings, the Klinjau River in Muara Dun Village can be classified as having low water contamination level.